The bone yard eaudiobook Body farm series, book 6. - Bass, Jefferson (Body Farm, 2011)
The New York Times best-selling duo of Dr. Bill Bass and Jon Jefferson deliver a gripping tale from their Body Farm series. When a pair of ravaged human skulls turn up in the Florida panhandle, Dr. Bill Brockton launches an investigation that eventually points to the notorious North Florida Boys' Reformatory. The institution burned down four decades earlier, and now that Dr. Brockton is digging through the grounds, he's ruffled a few prominent feathers.